2023
DOI: 10.3390/s23010470
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Equipped UAS for Non-Contact Bridge Inspections: Field Application

Abstract: In the future, sensors mounted on uncrewed aerial systems (UASs) will play a critical role in increasing both the speed and safety of structural inspections. Environmental and safety concerns make structural inspections and maintenance challenging when conducted using traditional methods, especially for large structures. The methods developed and tested in the laboratory need to be tested in the field on real-size structures to identify their potential for full implementation. This paper presents results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, it was found that the accuracy of UAV-based deflection measurements are dependent on the accuracy of the UAV movement. Garg et al [249,263], Nasimi and Moreu [248,264] and Nasimi et al [265] studied the effect of UAV movement in the accuracy of displacement measurements both indoor and outdoor in the context of bridges SHM and railroad bridge management. For additional commentary on the accuracy and sensitivity of UAVs for civil SHM, the reader is suggested to view Sreenath et al [266].…”
Section: Statusmentioning
confidence: 99%
“…However, it was found that the accuracy of UAV-based deflection measurements are dependent on the accuracy of the UAV movement. Garg et al [249,263], Nasimi and Moreu [248,264] and Nasimi et al [265] studied the effect of UAV movement in the accuracy of displacement measurements both indoor and outdoor in the context of bridges SHM and railroad bridge management. For additional commentary on the accuracy and sensitivity of UAVs for civil SHM, the reader is suggested to view Sreenath et al [266].…”
Section: Statusmentioning
confidence: 99%
“…By using drones for deploying vibration sensors that can perform on-device data processing, there exists an opportunity to deepen our understanding of structural dynamics under challenging conditions. 3,4 Current approaches in SHM have seen significant advancements through the integration of UAVs, edge computation, and SHM measurement techniques. 5 UAV-based remote sensing has emerged as a vital approach for bridge condition assessment, offering an efficient, cost-effective, and accessible means to inspect and monitor the structural health of bridges and other infrastructures.…”
Section: Introductionmentioning
confidence: 99%